LEVERAGING PBWORKS TO FOSTER COLLABORATIVE WRITING SKILLS AMONG UNDERGRADUATE IN FEDERAL POLYTECHNIC, UGEP, CROSS RIVER STATE, NIGERIA (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
This study explores the efficacy of PBworks, a web-based collaborative platform, in enhancing collaborative writing skills among undergraduate students at Federal Polytechnic, Ugep, Cross River State, Nigeria. Utilizing a quasi-experimental design, the research engaged 80 undergraduates from diverse academic disciplines in a 12-week intervention. The experimental group used PBworks for collaborative writing tasks, while the control group employed traditional face-to-face methods. Data were collected through pre- and post-intervention writing assessments, focus group discussions, and surveys. Findings revealed a significant improvement in the experimental group’s writing proficiency (MD = 16.72, t(78) = 7.124, p < .05) and collaborative skills, with enhanced peer interaction and feedback quality. Demographic analysis indicated no significant influence of gender or age on outcomes, though academic discipline moderately affected engagement levels. The study underscores PBworks’ potential to foster collaborative learning in resource-constrained settings, recommending its integration into Nigerian polytechnic curricula to enhance writing skills and teamwork. Limitations include technological access barriers and the study’s single-institution focus. Future research should explore longitudinal impacts and scalability across diverse institutions.